The relationship between water intake and progressivity glomerular filtration rate of chronic kidney disease patients. - MUNAQUISAH, Munaqisah; A RASYID, Haerani; AMINUDDIN, _; AS'AD, Suryani; TASLIM, Nurpudji A.; ASHARI, Nur (Nutrición Clínica y Dietética Hospitalaria, 2024)
Introduction and Objectives: Chronic kidney disease often accompanies hypertension and diabetes, necessitating strict medication regimens, dietary controls, and fluid restrictions. Dietary adjustments can reduce mortality and morbidity risks. In Indonesia, studies have investigated the link between water intake and CKD progression, emphasizing the importance of balanced fluid consumption. Our research aims to clarify water intake's significance for educating CKD patients. Methods: This prospective observational study entails the enrollment of CKD stage 3a, 3b, and 4 outpatients from the Hypertension Kidney Polyclinic at Dr. Wahidin Sudirohusodo Hospital in Makassar and the Makassar Satellite Hospital (comprising 10 participants) over a duration of 3 months. Participants maintain detailed records of average daily water intake and 24-hour urine volume in food diaries. Urea/creatinine (GFR) levels are assessed via blood samples, while urine osmolarity is determined from 24-hour urine collections. Results: Analysis of the research findings reveals a correlation coefficient of 0.151 between average daily water intake and delta creatinine, yielding a p-value of 0.677. A p-value exceeding 0.05 suggests insignificance in the correlation. Likewise, the correlation coefficient between average daily water intake and glomerular filtration rate delta is -0.196, with a corresponding p-value of 0.588, indicating no significant correlation. Conversely, the correlation coefficient between average daily water intake and total 24-hour urine volume stands at 0.625, yielding a p-value of 0.053. A p-value below 0.05 suggests significance in the correlation. Conclusions: Regrettably, this study fails to substantiate the research hypothesis concerning the association between water intake and 24-hour urine volume, urine osmolality, and GFR progression among CKD stage 3a, 3b, and 4 patients, owing to inherent research limitations